2022
DOI: 10.5853/jos.2021.03846
|View full text |Cite
|
Sign up to set email alerts
|

CT- versus MRI-Based Imaging for Thrombolysis and Mechanical Thrombectomy in Ischemic Stroke: Analysis from the Austrian Stroke Registry

Abstract: Background and Purpose It is unclear whether a particular stroke imaging modality offers an advantage for the acute stroke treatment. The aim of this study was to compare procedure times, efficacy and safety of thrombolysis and/or thrombectomy based on computed tomography (CT) versus magnetic resonance imaging (MRI) acute stroke imaging.Methods Data of stroke patients who received intravenous thrombolysis (IVT) and/or mechanical thrombectomy (MT) were extracted from a nationwide, prospective stroke unit regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In clinical trials and the real world, computed tomography (CT) perfusion or angiography is the mainstay due to its faster scan time. 4, 5, 22, 23 It has been hypothesized that CT-based decision making improves clinical outcome compared to MRI-based decision making since the time between stroke onset and reperfusion is the most crucial factor in determining stroke patients ‘ outcomes. 24 Nonetheless, accumulating evidence from real-world data has demonstrated that decisions based on MRI are not inferior to those based on CT, 22, 23, 25 despite not having been demonstrated in randomized clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical trials and the real world, computed tomography (CT) perfusion or angiography is the mainstay due to its faster scan time. 4, 5, 22, 23 It has been hypothesized that CT-based decision making improves clinical outcome compared to MRI-based decision making since the time between stroke onset and reperfusion is the most crucial factor in determining stroke patients ‘ outcomes. 24 Nonetheless, accumulating evidence from real-world data has demonstrated that decisions based on MRI are not inferior to those based on CT, 22, 23, 25 despite not having been demonstrated in randomized clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…4, 5, 22, 23 It has been hypothesized that CT-based decision making improves clinical outcome compared to MRI-based decision making since the time between stroke onset and reperfusion is the most crucial factor in determining stroke patients ‘ outcomes. 24 Nonetheless, accumulating evidence from real-world data has demonstrated that decisions based on MRI are not inferior to those based on CT, 22, 23, 25 despite not having been demonstrated in randomized clinical trials. In addition, precise infarct segmentation without inter- or intra-rater variability enables investigations on serial DWIs, infarct progression prediction, and infarct–functional anatomy connection.…”
Section: Discussionmentioning
confidence: 99%
“…6 Although the routine use of cerebral embolic protection devices remains controversial, 7 its use may be warranted for patients with marked valvular calcification. While the choice of imaging modality for MT (i.e., CT vs. MRI) may not influence the patient outcomes in ordinary ischemic stroke patients 8 and the modality with the greater impact on the selection of major treatment strategies better be chosen in principle, CT/CTA may be given priority in the initial evaluation of patients suspected of post-TAVI stroke, considering poor detectability of calcification on MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Although the routine use of cerebral embolic protection devices remains controversial, 7 its use may be warranted for patients with marked valvular calcification. While the choice of imaging modality for MT (i.e., CT vs. MRI) may not influence the patient outcomes in ordinary ischemic stroke patients 8 and the modality with the greater impact on the selection of major treatment strategies better be chosen in principle, CT/CTA may be given priority in the initial evaluation of patients suspected of post‐TAVI stroke, considering poor detectability of calcification on MRI. Mechanical thrombectomy, particularly the combined technique, remains the mainstay of treatment for calcified cerebral embolus, 9 and surgical embolectomy may be considered as a rescue measure for those with a large calcified embolus refractory to MT, 10 as seen in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the subjective perception of timely vessel imaging evaluation by either magnetic resonance imaging (MRI) or especially CTA, current data show that patients in whom CTA is performed before transfer to the EVT center from a primary stroke center have a time delay of at least 62 min [15] This aligns with a 24 min delay reported by a high-volume, efficient, comprehensive stroke center in Barcelona, Spain [16] . Furthermore, expected treatment delays with MR-based imaging are approximately 20 min more than for CT-based protocols [17] .…”
Section: Dtasmentioning
confidence: 99%